Autistic Employees in Canadian Academic Libraries: Barriers, Opportunities, and Ways Forward - Giles-Smith, Lori; Popowich, Emma (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2023)
There is little research on the employment of autistic librarians and library support staff, and yet there are many ways in which libraries are a good fit for autistic individuals. As the prevalence of autism grows, academic libraries represent a viable option for meaningful and inclusive employment for autistic employees, provided library managers and administrators create environments that value diversity and inclusion. The main purpose of this study was to obtain information from autistic staff currently or recently employed in academic libraries in Canada about the current difficulties and barriers they experience in the workplace, the opportunities that working in a library gives to autistic employees, and potential accommodations they feel would allow them to excel and thrive in their workplaces. A questionnaire was developed to collect the data, designed to respond to our research questions. Through qualitative analysis we identified the following themes in the survey results: library as unsafe space, social difficulties in the workplace, difficulties requesting accommodations, and a need for improved understanding of autism.